2020
DOI: 10.1021/acsami.0c08307
|View full text |Cite
|
Sign up to set email alerts
|

Structural-Defect-Mediated Grafting of Alkylamine on Few-Layer MoS2 and Its Potential for Enhancement of Tribological Properties

Abstract: Two-dimensional transition-metal dichalcogenides possess inherent structural characteristics that can be harnessed for enhancement of tribological properties by making them dispersible in lube media. Here, we present a hydrothermal approach to preparing MoS2 nanosheets comprising 4–10 molecular lamellae. A structural-defect-mediated route for grafting of octadecylamine (ODA) on MoS2 nanosheets is outlined. The unsaturated d orbitals of Mo at the sulfur vacancies on the MoS2 surface are coupled with the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…The peak at 168.78eV indicates the existence of SO 4 2species and confirms the partial oxidation of MoS 2 surface in contact with air [48]. The binding energies of Mo 3d and S 2p are in good agreement with the reported values for MoS 2 particles [49,50,29].…”
Section: Fig 3 Tem Images Of the Mos 2 Nanoparticles (Sample Eg1w4)supporting
confidence: 78%
See 1 more Smart Citation
“…The peak at 168.78eV indicates the existence of SO 4 2species and confirms the partial oxidation of MoS 2 surface in contact with air [48]. The binding energies of Mo 3d and S 2p are in good agreement with the reported values for MoS 2 particles [49,50,29].…”
Section: Fig 3 Tem Images Of the Mos 2 Nanoparticles (Sample Eg1w4)supporting
confidence: 78%
“…Furthermore, the average friction coefficient, the average wear scar diameter and the performance at extreme pressure of ODAB-MoS 2 -based oil were improved by approximately 27.9%, 22.9% and 17.4%, respectively, compared to the base oil. Kumari et al [29] successfully functionalized the surface of MoS 2 nanosheets with octadecylamine (ODA) and demonstrated that sulfur vacancies and structural defects on the surface of MoS 2 nanosheets facilitate the grafting of ODA and ensure good dispersibility in mineral oil, resulting in a significant reduction in friction (48%) and wear (44%).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the normal stress of MoS 2 lubrication system was relatively stable with a lower average value. This is because the soft MoS 2 was prone to deformation, and the intermolecular force between MoS 2 nanosheets was very weak, hence a portion of the normal pressure was suffered by the NPs [25,41]. Finally, the change in the stress transmitted to rigid layers was less obvious.…”
Section: Friction Properties Of Different Nanoparticlesmentioning
confidence: 99%
“…The CTA cation grafted over the h-BNNSs could be mechanically detached at the molecular level because of the significantly high contact stress (3.44 GPa; corresponding to an applied load of 392 N) between the steel balls. 67 The sliding stress-induced desorption/wearing of CTA cations having highly polar groups (nitrogen element) are believed to interact efficiently with steel contact interfaces and contribute to forming protective tribo thin films of low shear strength. 71 These results revealed that a continuous supply of h-BNNS-CTAB, low shear strength, and the deposition of lubricious thin film on tribo interfaces play important roles in decreasing the friction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%